2022
DOI: 10.1177/13591045221111848
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of preschool children with obsessive compulsive disorder

Abstract: The aim was to examine the clinical features of Obsessive-Compulsive Disorder (OCD) in preschool and the effectiveness of aripiprazole with a standardized Cognitive-Behavioral Family Therapy (CBFT) in the treatment of preschoolers with OCD. Twelve preschool children, 36–72 months of age were diagnosed with OCD according to the Diagnostic and Statistical Manual of Mental Disorders, the Fifth Edition criteria by a fellowship-trained child and adolescent psychiatrist. They were evaluated with Kiddie Schedule for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Also, of the 19 studies included in the review, 15 reported providing six or fewer sessions of EMDR (mean = 2.28 sessions), with five of these studies providing only one EMDR session. Another study that includes adolescents with panic disorder also indicated significant improvement in adolescents with panic disorder at the end of the fourth week of EMDR (Inci Izmir et al, 2023). These previous studies showed that short therapy sessions could be effective.…”
Section: Resultsmentioning
confidence: 82%
“…Also, of the 19 studies included in the review, 15 reported providing six or fewer sessions of EMDR (mean = 2.28 sessions), with five of these studies providing only one EMDR session. Another study that includes adolescents with panic disorder also indicated significant improvement in adolescents with panic disorder at the end of the fourth week of EMDR (Inci Izmir et al, 2023). These previous studies showed that short therapy sessions could be effective.…”
Section: Resultsmentioning
confidence: 82%
“…Researchers previously used the term CDS as a sub-concept of ADHD to define ADHD cases where inattention is predominant, focusing particularly on whether it can be distinguished from inattentive ADHD symptoms (Leopold et al, 2015; McBurnett et al, 2001). Today, while some researchers claim that CDS often accompanies ADHD, but it is a different condition, others argue that we do not yet have enough evidence to call CDS a disorder (Barkley, 2014; Becker et al, 2023; Kofler et al, 2019; Uzun Cicek et al, 2023; Willcutt et al, 2014). Indeed, several studies suggested that ADHD and CDS are frequently seen together.…”
Section: Discussionmentioning
confidence: 99%